Criminal Sanctions for Unauthorized Transportation of Protected Animals: Perspective of the Purpose of Punishment - Achmad Nazir Thaharah (Administrative and Environmental Law Review, 2023)
The trade of protected wildlife has a detrimental impact on the sustainability of endangered wildlife populations in Indonesia. Criminal punishment against the perpetrators of the crime of transportation of animals for the purpose of trade must be able to provide a deterrent effect and benefits for the protection of animals. The imposition of punishment in the criminal act of transportation of protected wildlife needs to be examined further from the aspect of the purpose of punishment, which is to prevent criminal acts by enforcing legal norms for the protection of society. This article will discuss the basic considerations of judges in punishing perpetrators of criminal acts without the right to transport protected animals alive. And the imposition of punishment by the judge against the perpetrator of the crime is in accordance with the purpose of punishment or not. The research method uses normative research methods, with literature studies in the form of laws and regulations related to the issues discussed. Based on the results of the research, as in Decision Number: 77/Pid.B/LH/2020/PN.Tjk, the punishment of the perpetrators of the criminal act of transporting protected wildlife in a live state is based on juridical, sociological, and philosophical considerations. The author recommends that perpetrators of protected wildlife trade be sentenced to heavy fines because their actions are economically motivated. In addition, it is necessary to regulate social work sanctions for convicted poachers and protected wildlife traffickers to restore the consequences of the criminal acts that have been committed.